Effect of Applied Current Density of Plasma Electrolytic Oxidation Process on Corrosion Resistance of AZ31 Magnesium Alloy - Kajanek, Daniel; Hadzima, Branislav; Brezina, Matej; Jackova, Martina (Communications - Scientific letters of the University of Zilina, 2019)
Impact of applied current density during the plasma electrolytic oxidation (PEO) process on corrosion resistance of AZ31 magnesium alloy was studied. The PEO coatings were prepared using four different current densities with values of 0.025 A/cm2, 0.05 A/cm2, 0.1 A/cm2 and 0.15 A/cm2 in electrolyte consisting of 10 g/l Na 3PO4.12H2O and 1 g/l KOH. Morphology and chemical composition of the coatings was examined using the scanning electron microscopy and EDS analysis respectively. Electrochemical characteristics of ground and coated samples were measured by means of electrochemical impedance spectroscopy (EIS) in 0.1M NaCl solution. Obtained data in form of Nyquist diagrams were analysed by equivalent circuit method. Results of experiments showed that value of applied current density had significant effect on protective performance of the PEO coatings prepared on AZ31 magnesium alloy surface.